Potential Effects of Some Factors on Psoriasis Course in Children - Svetlana G. Gubanova; Eduard T. Ambarchyan; Leyla S. Namazova-Baranova; Elena A. Vishneva; Irina V. Zelenkova; Viktor A. Gankovskiy; Nataliya L. Aleshenko; Elena V. Kaytukova; Anastasiya D. Kuzminova; Vladislav V. Ivanchikov (Педиатрическая фармакология)
Psoriasis is the second most common skin disease after atopic dermatitis in childhood. There are factors affecting both the manifestation and aggravation of this inflammatory skin process. The leading role in the psoriasis pathogenesis is currently associated with key cytokines. However, infectious diseases could be the triggers for psoriasis.Nowadays, the approach to psoriasis management in children has been revised due to emerging of new knowledge about the clinical manifestations and the role of numerous comorbid conditions in psoriasis course. Risk factors assessment, as well as evaluation of potential comorbidities signs and symptoms, is crucial part in patient management to create a prognostic model of the disease progression and the aggravation development (with underlying associated inflammatory processes included).